Green Bonds: Opportunities and Challenges for Reconciling Ethics and The International Financial System - Lechini, Gladys Teresita (2025)
In recent years, there has been a development of innovative instruments in order to increase the resources allocated to the fight against climate change. Within this emerging trend, green bonds are a specific instrument oriented towards financing certified climate-sustainable projects. Rather than perceiving these instruments as a trivial response or a means of exonerating public responsibilities, political and economic decision-makers must recognise the relevance of green bonds and establish a robust regulatory framework around these specific instruments.This chapter aims to analyze the opportunities and challenges presented by green bonds in bridging the financial and ethic worlds. Based on this main objective, this chapter attempts to contribute to the design and implementation of international and national regulatory frameworks for green bonds and “labelled bonds”, in general.